A Comparative Study of Hole Integrity Performance in Composite-Metal Stacks Using Coated and Uncoated Tungsten Carbide Drill Bits - Joy Mathavan, J.; Hafiz Bin Hassan, M.; Bin Mahmud, A.S. (Wiley Online Library, 2023)
This study aims to develop tetrahedral amorphous carbon nanocomposite layer coated tungsten carbide drill bits for single shot drilling of composite metal stack. Different coatings were tested for hole integrity performance compared to an uncoated tool and the results were validated using process capability six-pack analysis. The drilling process employed a 4.85 mm twist drill with a feed rate of 0.05 mm/rev and spindle speed of 2600 rev/min. The experimental results indicate that, all the coated tools produce H9 tolerance holes while uncoated tool produced H7 tolerance holes with 18 % to 35 % better results. But statistical results show that all the tools including uncoated tool require improvement to stay within the control limits. The hole circularity error obtained by all the tools were below 24 μm in both the panels and is supported by the statistical results as well. The uncoated tool exhibited 17.91 % better surface roughness in aluminium panel compared to coated tools, while coated tools produced 17.2 % to 22.3 % better surface roughness in composite panel. Statistical results suggested that, improvement is necessary when drilling aluminium panel by all the tools while dopant added coated tools produce better results in composite panel.
Keywords: Composite metal stacks; Tetrahedral amorphous carbon coating; Process capability six pack analysis; Hole integrity performance; Single shot drilling